2012
DOI: 10.4161/cc.11.3.19024
|View full text |Cite
|
Sign up to set email alerts
|

The Janus face of OSM-mediated cardiomyocyte dedifferentiation during cardiac repair and disease

Abstract: (2012) The Janus face of OSM-mediated cardiomyocyte dedifferentiation during cardiac repair and disease, Cell Cycle, 11:3,[439][440][441][442][443][444][445]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Similarly, significant accumulation of FGF23 was observed in cardiomyocytes of patients with myocarditis, ischemic and dilative cardiomyopathy. We therefore suggest the following mechanism of FGF23 expression and secretion: Monocytes/macrophages invade the myocardium after an initial injury and release oncostatin M which induces a "cell survival program" via the oncostatin M receptor-β [6,9]. Under chronic extension of low level inflammation cardiomyocytes are constantly stimulated and produce FGF23 even if the myocardial performance deteriorates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, significant accumulation of FGF23 was observed in cardiomyocytes of patients with myocarditis, ischemic and dilative cardiomyopathy. We therefore suggest the following mechanism of FGF23 expression and secretion: Monocytes/macrophages invade the myocardium after an initial injury and release oncostatin M which induces a "cell survival program" via the oncostatin M receptor-β [6,9]. Under chronic extension of low level inflammation cardiomyocytes are constantly stimulated and produce FGF23 even if the myocardial performance deteriorates.…”
Section: Discussionmentioning
confidence: 99%
“…They convincingly demonstrate that the over expression or mutation of a single cytokine/ chemokine/growth factor, a corresponding receptor or intracellular signalling molecule is sufficient to evoke HF [5][6][7]. However, these signalling cascades are not detrimental per se but constitute an evolutionary conserved defence mechanism [6,8,9]. Since the initiated "cell survival program" might turn into a "cell death program" by chronic activation, the blockade of cytokine/growth factor controlling signalling cascades becomes a promising therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…It was first identified as a secreted product of macrophage-like cells that inhibited proliferation of melanoma-, neuroblastoma-, and lung cancer-derived cell lines (2), and although it suppresses breast cancer cell proliferation (3), it has been suggested to support metastasis of breast cancer in the skeleton due to proosteoclastic activities (4) and to stimulate Kaposi's sarcoma (5). Studies in knock-out mice have shown that OSM supports hematopoiesis (6) and bone formation at the expense of adipogenesis (7), but it has also been implicated in pulmonary tissue fibrosis (8), cardiac disease and repair (9), prostate cancer (10), asthma (11), periodontal disease (12), and both rheumatoid and osteoarthritis (13).…”
Section: Oncostatin M (Osm)mentioning
confidence: 99%
“…In contrast to these early roles, OSM also has stimulatory roles in a number of human cancers including Kaposi's sarcoma 2 and breast cancer. 3 Frequently acting in conjunction with inflammatory factors or other gp130-dependent cytokines, OSM has been implicated in diverse disorders including pulmonary tissue fibrosis, 4 cardiac disease and repair, 5 prostate cancer, 6 asthma, 7 periodontal disease 8 and both rheumatoid arthritis and osteoarthritis. 9 In the context of skeletal biology, OSM is of particular interest as it displays anabolic effects on both cortical and trabecular bone (which would be clinically desirable to emulate) while at the same time driving osteoclast formation; notably, both influences are at least in part mediated by OSM action on the osteoblast lineage.…”
mentioning
confidence: 99%